Long term side effects of methylphenidate hydrochloride in childhood ADHD in primary care: An evidence-based case report - Andoko, Dewanto; Lumbuun, Nicolaski; Cipta, Darien (Bahasa Indonesia, 2024)
Background: Attention Deficit Hyperactivity Disorder (ADHD) often emerges in childhood and can persist into adolescence and adulthood. Methylphenidate is the primary medication for managing ADHD in youth, but its long-term effects remain uncertain. Evaluating the evidence on the long-term effects of methylphenidate in children with ADHD is crucial. Case: A 7-year-old with school difficulties, hyperactivity, and distractibility (Conner's score 22) was diagnosed with ADHD and treated with methylphenidate. Significant behavioral improvement was observed (Conner's score 8), but parental concerns regarding long-term medication use persisted. Metode: We conducted a structured search in PubMed, EBSCOhost, Cochrane, and SAGE databases, focusing on the past 5 years of English-language human studies with full-text availability. We selected randomized control trials (RCTs), meta-analyses, and systematic reviews and screened them based on relevance to our clinical question. The search yielded results from PubMed (43 articles), EBSCOhost (46 articles), Cochrane (41 articles), and SAGE (125 articles). After rigorous screening, some articles were identified as relevant. Conclusion: Our case analysis based on evidence revealed that methylphenidate treatment is associated with serious and non-serious side effects, irrespective of treatment duration. Primary care clinicians should exercise caution when prescribing methylphenidate for ADHD management in childhood.